COMBINATION OF THE ISOCHORIC METHOD AND THE EXPANSION METHOD TO DETERMINE DENSITIES OF HYDROGEN AT TEMPERATURES UP TO 500°C - Supriatno Supriatno (SINERGI, 2018)
Utilization of hydrogen as an alternative fuel is promising because it is environmentally friendly. Hydrogen system design requires accurate hydrogen densities. The density of hydrogen is determined based on experimental data. For gases that have a low density such as hydrogen, the effective measurement method is required. An apparatus has been designed to measure PVT properties of hydrogen at pressures up to 1 MPa and temperatures up to 500ºC. The apparatus uses a combination of isochoric and expansion methods. The method doesn’t need a measurement of pressures and temperatures along the isochoric line as required usually in the isochoric conventional method. Moreover, it doesn't need direct measurements of gas mass and gas volume. The volume was determined by measuring nitrogen at a pressure of 0.5 MPa and at temperatures up to 500ºC and by using Span’s equation of state. Measurements of hydrogen have been performed at a pressure up to 0.7 MPa and temperatures up to 498.217ºC. Densities of hydrogen obtained from the present measurement are compared with that obtained from calculation of Leachman's equation of state. Maximum deviation is 1.42% at a temperature of 498.217ºC and at a pressure of 0.2947 MPa and minimum deviation is 0.11% at temperature and pressure of 399.461ºC and 0.6981 MPa respectively.